A qualitative study of motivations for non-suicidal self-injury in a sample of psychiatric outpatients in Singapore - Shazana Shahwan; Yunjue Zhang; Rajeswari Sambasivam; Say How Ong; Siow Ann Chong; Mythily Subramaniam (Singapore Medical Journal)
Introduction: The popular notion that the need for attention drives non-suicidal self-injury (NSSI) serves to stigmatise rather than understand this warning sign of underlying psychological/psychiatric disorder. Despite the pervasiveness of NSSI in clinical and community settings, effective treatments for this behaviour are lacking. This qualitative research aims to understand the motivations of NSSI in adolescents/young adults in a mental health facility in Singapore. Methods: Semi-structured interviews were conducted with 20 outpatients (6 males, 14 females) of the Institute of Mental Health aged 17–29 years who had reported NSSI as part of an earlier survey. The interviews were audio-recorded and transcribed verbatim. Thematic analysis was used to analyse the data. The main themes and sub-themes were identified and described. Results: A preponderance of motivations served intrapersonal emotion-regulating purposes, which were categorised as to: (a) release bottled-up feelings; (b) self-punish; (c) turn aggression inwards; (d) sensitise oneself; and (e) attain a sense of control and mastery. By contrast, a small subset of motivations served the interpersonal motivation of signaling one's distress, especially when the capacity for verbal expression was limited or attempts to verbalise distress were futile. Conclusion: Committing NSSI solely for attention-seeking is a myth that perpetuates the stigma and hinders those in need of psychological care from seeking appropriate treatment. NSSIs may be warning signs that indicate not only intrapersonal conflicts but external environments that are perceived unsafe to deal with these intrapersonal conflicts. An understanding of the underlying motives will facilitate better treatment of individuals presenting with NSSI.